2007
DOI: 10.1002/cne.21230
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for multiple signaling pathways in single squid olfactory receptor neurons

Abstract: At least two different G-protein-mediated transduction cascades, the adenylate cyclase and phospholipase C (PLC) pathway, process chemosensory stimuli for various species. In squid olfactory receptor neurons (ORNs), physiological studies indicate that both pathways may be present; however, confirmation of the transduction molecules at the protein level is absent. Here we provide evidence that the G-proteins involved in both adenylate cyclase and PLC pathways are present in squid ORNs (Lolliguncula brevis). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…The anatomical descriptions of a putative olfactory organ in cephalopods first appeared in early literature (von Kölliker, 1844), followed by more recently demonstrations of their chemosensory capabilities and sensory mechanisms. To date, what is known about the olfactory organ in cephalopods comes from studies of Nautilus (Basil et al, 2000;Ruth et al, 2002) and decapods (Lucero and Gilly, 1995;Lucero et al, 1992Lucero et al, , 2000Mobley et al, 2007Mobley et al, , 2008aPiper and Lucero, 1999;Villanueva and Norman, 2008). In squid the olfactory organ is the site of a sensory epithelium resulted of ciliated supporting cells and different types of receptor cells that are bipolar neurons sending an dendritic stalk branch to the surface of the epithelium where sensory cilia are exposed to the marine environment.…”
Section: Olfaction In O Vulgarismentioning
confidence: 97%
See 1 more Smart Citation
“…The anatomical descriptions of a putative olfactory organ in cephalopods first appeared in early literature (von Kölliker, 1844), followed by more recently demonstrations of their chemosensory capabilities and sensory mechanisms. To date, what is known about the olfactory organ in cephalopods comes from studies of Nautilus (Basil et al, 2000;Ruth et al, 2002) and decapods (Lucero and Gilly, 1995;Lucero et al, 1992Lucero et al, , 2000Mobley et al, 2007Mobley et al, , 2008aPiper and Lucero, 1999;Villanueva and Norman, 2008). In squid the olfactory organ is the site of a sensory epithelium resulted of ciliated supporting cells and different types of receptor cells that are bipolar neurons sending an dendritic stalk branch to the surface of the epithelium where sensory cilia are exposed to the marine environment.…”
Section: Olfaction In O Vulgarismentioning
confidence: 97%
“…Olfaction plays a role in mate choice of squid and cuttlefishes (Cummins et al, 2011;Gilly and Lucero, 1992;Lucero and Gilly, 1995;Lucero et al, 1992Lucero et al, , 2000Mobley et al, 2007;Piper and Lucero, 1999;Zatynly et al, 2000) and improves predation on crabs by cuttlefishes (Boal et al, 2000). Nautilus use olfaction for distant food odour detection and location, and perhaps for mate choice (Basil et al, 2000;Ruth et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Based on studies showing that sensory neurons with different structures are receptive to different classes of odorants (bile acids, amino acids; Hansen et al,2003), and express different transduction molecules (Hansen et al,2004,2005; Mobley et al,2007), we hypothesized that squid ORN types have different but overlapping odor specificities. To study the odor responsiveness of all of the squid ORN types, we used the activity marker, agmatine (AGB), on intact squid olfactory organs.…”
mentioning
confidence: 99%
“…In mammals the odorant ligand(s)-receptor interactions cause an activation of downstream effectors via G proteins, which can regulate a variety of effectors such as cAMP and inositol 1,4,5-trisphosphate [Ins(1,4,5)P 3 ], whereas the functional insect olfactory receptor consists of a heteromeric complex forming a ligand-gated ion channel (Sato et al, 2008). Although relatively little is currently known about the molecular mechanism of chemical detection in molluscs, including the identity of chemoreceptors, recent olfactory studies in squid have shown that in olfactory receptor neurons, both phospholipase c (PLC) and cAMP-mediated pathways may be involved in signal processing (Mobley et al, 2007). In our studies of the marine opisthobranch mollusk Aplysia californica, we isolated a full-length cDNA from a central nervous system (CNS) cDNA library that encodes a protein homologous to the G protein alpha subunit G q (DQ397515), as well as a phospholipase C (PLC; DQ397516) and an inositol 1,4,5-trisphosphate receptor (Ins(1,4,5)P 3 R; DQ397517) (Cummins et al, 2007).…”
Section: Introductionmentioning
confidence: 99%